2016
DOI: 10.1590/abd1806-4841.20165071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic urticaria on the quality of life of patients followed up at a university hospital

Abstract: BACKGROUNDChronic urticaria is a debilitating disease that considerably affects health-related quality of life, and the Chronic Urticaria Quality of Life Questionnaire is the only questionnaire specifically designed for its evaluation.OBJECTIVETo evaluate the quality of life of patients with chronic urticaria, using the Brazilian Portuguese version of the Chronic Urticaria Quality of Life Questionnaire.METHODSThe Chronic Urticaria Quality of Life Questionnaire was self-administered in 112 chronic urticaria pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 28 publications
(30 reference statements)
3
41
0
10
Order By: Relevance
“…The higher mean DLQI (12.1) and CU‐Q2oL (54.4) scores in the current study might be attributed to the inclusion of patients with more severe and recalcitrant disease. Consistently with the existing data, the most affected subdomains were work/school and symptoms/feelings for DLQI, and sleep and pruritus for CU‐Q2oL in the present study (Dias et al, ; Liu et al, ; Maurer, Abuzakouk, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The higher mean DLQI (12.1) and CU‐Q2oL (54.4) scores in the current study might be attributed to the inclusion of patients with more severe and recalcitrant disease. Consistently with the existing data, the most affected subdomains were work/school and symptoms/feelings for DLQI, and sleep and pruritus for CU‐Q2oL in the present study (Dias et al, ; Liu et al, ; Maurer, Abuzakouk, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This confirms a significantly impaired QoL in the wide spectrum of CU patients, as well as in the specialized centers that have been previously reported. 6,27,28 In addition, this RELEASE study evaluated disease control of urticaria using UCT for the first time in Japan and revealed that approximately 64% of CU patients at the time of survey displayed a UCT score of less than 12, indicating uncontrolled symptoms. Those CU patients with lower UCT scores showed higher DLQI total scores compared with patients with high UCT scores.…”
Section: Discussionmentioning
confidence: 99%
“…13 Valero et al observaron una proporción de mujeres de 62.1 %, 14 mientras que Dias registró 85.7 %. 16 Se acepta que la razón mujer:hombre es de 2:1, ligeramente mayor a la encontrada en nuestro estudio. 17 La media de la edad en nuestro estudio fue de 39.9 años ± 15.6, similar a los 33.9 años ± 16.8 en el estudio de Hernández Ochoa y a 35.8 años ± 18.9 informada por Ferrer.…”
Section: Discussionunclassified
“…Este promedio corresponde a "un poco" de afectación en la calidad de vida, que se observó en 66.7 % de los pacientes de nuestro estudio. Se ha identifi cado que los pacientes refi eren mayor afectación en los parámetros referentes a prurito y problemas de sueño por sobre el edema, actividades, limitaciones y aspecto/imagen, 14,16 con porcentajes similares a los reportados por nuestro equipo: 46.5 y 26.2% para prurito y problemas de sueño, respectivamente.…”
Section: Discussionunclassified